The nonlinear amplification of magnetic fields by cosmic rays at supernova remnant shocks - Reville, B; Duffy, P; O'Sullivan, S (2006)
A central problem in the theory of cosmic ray acceleration at supernova shock fronts is the generation of turbulent magnetic fields needed to scatter particles across a shock front. In this paper we build on previous studies [1], [2] into the effect of streaming cosmic rays produced by the outer shocks of supernova remnants on the stochastic component of the magnetic field. A three dimensional, MHD code has been constructed which demonstrates the nonlinear growth of the turbulent field.